Mulheres, feministas e leitoras: uma análise de discursos sobre a leitura em sites feministas - Vela, Giovana Amorim Zago (Universidade Federal de São Carlos, 2021)
This research aims to analyze reading indications of works aimed at the public segment that would identify itself as a feminist, to understand these statements certain representations of reading and that reading public. For this, we use a corpus made up of statements from texts from different origins, published in personal or institutional blogs, whose common theme is the indication of books from the feminist segment, to observe which titles and authors are indicated, which comments accompany these lists with indications. In these texts, there is mention of titles and authors considered as feminists, whose reading is recommended, and which are characterized by the publications, comments, and opinions that they express about these texts and authors read and indicated. In these magazines, comments, and opinions, it expresses what it considers to be of interest to this “reading community”, as well as mentioning the importance of reading in general, and reading these works in a specific way. When referring to reading, they sometimes affirm the role of this practice as a means of personal emancipation, as a way of engaging in a collective struggle, and as a source of empowerment in the feminist cause. Our research consists, therefore, in the survey and analysis of these statements present in these diverse sources that have in common feature referring to reading, books and authors that interest those who identify with the theme of feminism, to provide us with clues about aspects of the reader profile of that community, indicated in these texts. In our analysis, we will be based theoretically and methodologically on the principles of Discourse Analysis, using the concept of “genres of discourse” by Mikhail Bakhtin, and the functioning of utterances, as described by Michel Foucault in his “order of discourses”. Regarding studies on the practice of reading, we rely on cultural history, especially on the studies developed by Roger Chartier on reading and readers.
Women, feminists and readers: an analysis of discourses about reading on feminist websites
Femmes, féministes et lectrices : une analyse des discours sur la lecture sur les sites féministes
Keywords: Discursos sobre a leitura; Mulheres leitoras; Feminismo; Sites feministas; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA